Integration of 68Ga-PSMA-PET imaging in planning of primary definitive radiotherapy in prostate cancer: a retrospective study. Issue 1 (December 2016) - Dewes, Sabrina; Schiller, Kilian; Sauter, Katharina; Eiber, Matthias; Maurer, Tobias; Schwaiger, Markus; Gschwend, Jürgen; Combs, Stephanie; Habl, Gregor
Abstract Background Prostate cancer (PC) is one of the most commonly treated cancer entities with radiation therapy (RT). Risk group-adapted treatment and avoidance of unnecessary toxicities relies primarily on accurate tumor staging. Thus, the introduction of prostate-specific membrane antigen (PSMA) in diagnosis and treatment of PC is a highly interesting development in radiation oncology of urologic tumors. The present work is to evaluate the integration of68 Ga-PSMA-PET imaging into standard radiation planning of primary definitive treatment of PC and to determine the impact of PSMA imaging on tumor staging. Methods The data of 15 patients treated for PC between August 2013 and April 2015 were evaluated. Treatment planning included68 Ga-PSMA-PET imaging. We analyzed whether the use of PSMA-imaging led to a change of the TNM stage and if it influenced the RT treatment approach or the target volume, due to changes in the gross tumor volume (GTV) or clinical target volume (CTV), in the final treatment plan. Results In 53.3 % of the analyzed patients a change occurred in the TNM stage based on68 Ga-PSMA-PET examination. The RT concept changed in 33.3 % of all patients, leading to relevant changes in the planning target volume. Among these, an additional irradiation of the pelvic lymph drainage due to tracer uptake in lymph nodes was performed in 25 %. Furthermore, boost volumes of PET-positive lymph nodes were added in 80 % of these cases. A down staging due to the68 Ga-PSMA-PET examination occurred in 13.3 % of all cases. Conclusions The integration of68 Ga-PSMA-PET-imaging into the RT treatment planning process can be useful for detailed target volume planning. The performance of a68 Ga-PSMA-PET frequently leads to changes in the TNM stage, altering the RT treatment regimen and the target volume. A prospective trial is underway to evaluate the impact of68 Ga-PSMA-PET based treatment planning on outcome.